A Review on the Current Scenario of Phytoremediation in Pakistan: Review on Phytoremediation in Pakistan (Biological Sciences - PJSIR, 2024)
Phytoremediation is a promising technique to clean the noxious contaminants from soil, air and water as the pollutants like heavy metals which severely affect the environment due to anthropogenic activities. Most of pollutants de-contamination methods are costly and have low performance. Phytoremediation is effective and affordable green technology which uses selected green plants. Different plants species experimentally proven to absorb different metals like Pb, Zn, As, Cd, Cr from contaminated sites. This review focuses on development of phytoremediation of metals from environmental compartments. The aim of this review to conduct the studies on phytoremediation in Pakistan in the last two decades phytoremediation has different mechanisms such as phytoextraction, phytodegradation, phytovolatilization, phytostabilization and Rhizofiltration. In Pakistan out of 400 plant species only 50 plant species were observed to clean contaminated soil, air and water. Heavy metals contamination has become most alarming problem worldwide. A previous study revealed about 1.7 billion places are affected from heavy metals contamination especially in developing countries. Metals are non bio-degradable and tend to bio-accumulate and biomagnify in food chain and linked with many diseases, their remediation using plants is economical and environmental friendly.